ANAlISIS FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KELELAHAN KERJA PADA PENGUMPUl TOL DI PERUSAHAAN PENGEMBANG JALAN TOL SURABAYA - Arini, Shintia Yunita; Dwiyanti, Endang (Universitas Airlangga, 2015)
ABSTRACTFatigue is one of the problems experienced often by workers. Feeling of fatigue is subjective because every person is influenced by several factors deserve and need special attention as a follow-up in order to avoid problems in the health of workers. Toll collector is one of the employees at toll road developer that has an important task in the operation of toll roads. The objective of this research to determine the relationship of several independent variables included age, gender, exercise habits, monotonous circumstances and workload, work climate and noise toward to the dependent variable, fatigue. This research was analytic observational methods of data collection and cross sectional design.. The sample in this study was a toll collector at one of toll road developer taken from the population using simple random sampling. Variable testing performed using spearman correlation analysis and contingency coefficient. Variables studied had a relationship with fatigue if p < 0.05. There are 34 workers (50.7%) had mild fatigue. Statistical analysis showed weak correlation to the variables gender (p = 0.004), exercise habits (p = 0.033), state of monotony (p = 0.008), work climate perception (p = 0.011) , and the noise perception (p = 0.033) of the relationship with the occurrence of fatigue. So fatigue was influenced by several factors such as individual factors, job factors, and work environmental factors.Keywords: fatigue, toll collector, subjective